IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP DISIPLIN APARATUR SIPIL NEGARA PADA KANTOR KELURAHAN BARANTI KABUPATEN SIDENRENG RAPPANG - Andi Asmawati (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
This study aims to determine the Implementation of Government Policy on the Discipline of State Civil Apparatus in the Village Office in Baranti District, Sidenreng Rappang Regency. The sampling technique used a saturated sampling technique with a total sample of 23 people. The technique of collecting data uses observation, interviews, questionnaires, and literature studies. Quantitative data analysis techniques used are frequency tabulation analysis and simple regression analysis with the help of SPSS 16.0 for windows and Likert Scale programs.Based on the results of the questionnaire, the recapitulation of the variable implementation of government policy was obtained, measured through appropriate policy indicators, appropriate implementers, right targets, right environment, and appropriate processes, 41% included in the "good enough" category. The recapitulation of the disciplinary variables of the state civil apparatus is measured through indicators of time discipline, regulatory discipline, responsibility discipline, 33% included in the "less good" category. Based on the results of processed simple regression analysis using SPSS 16.0 for windows, the Model Summary obtained avalue of 41% with the category "good enough".